KOKAPSTRĀDES UZŅĒMUMA NOTEKŪDEŅU RACIONĀLAS APSAIMNIEKOŠANAS TEHNOLOĢISKIE RISINĀJUMI - Lupiķis, Jānis; Noviks, Gotfrīds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The paper explores the possibilities to treat wastewater with electroflotation method. Wastewater from wood processing industry were treated on constructed laboratory electroflotator at different temperatures and time intervāls. Obtained optimal treatment regimes.